Are Solid Solutions Better in FeNbSb‐Based Thermoelectrics?. (22nd November 2016) - Fu, Chenguang; Liu, Yintu; Zhao, Xinbing; Zhu, Tiejun
Abstract : Forming solid solutions, due to its universal applicability, has been the most effective strategy for improving the performance of a wide variety of thermoelectric materials. Taking p‐type FeNb1− x V x Sb solid solutions as an example, here it is shown that the formation of solid solutions cannot always improve the thermoelectric performance. The peak zT and thermoelectric quality factor of p‐type FeNb1− x V x Sb decrease with increasing V content, remarkably different from other thermoelectric systems. The present results demonstrate that comprehensive understanding of the multiple effects of forming solid solutions is important for developing high‐performance thermoelectrics. Abstract : Taking p‐type FeNb1− x V x Sb solid solutions as a paradigm, it is shown that forming solid solutions is not always an effective strategy for improving the performance of thermoelectric materials due to its multiple effects on the transport properties. In‐depth understanding of the complex effects of solid solution formation is of great important for developing high‐performance thermoelectrics.